Beyond central adiposity: Liver fat and visceral fat area are associated with metabolic syndrome in morbidly obese patients. (February 2015) - Faria, G.; Gonçalves, A.; Cunha, R.; Guimarães, J.T.; Calhau, C.; Preto, J.; Taveira-Gomes, A.
Abstract: Background: Despite its widespread clinical use, both body mass index (BMI) and waist circumference have been reported as inaccurate methods to measure abdominal obesity. The main objective of this study was to determine the relation between visceral fat area and fatty liver infiltration with the expression of metabolic syndrome (MS) in morbidly obese patients. Methods: We recruited a random selection of 100 morbidly obese patients on pre-operative evaluation for bariatric surgery. A pre-operative CT slice at L4-L5 level, was performed to measure visceral fat and at T12 level to measure hepatic attenuation. Results: Patients with MS had lower hepatic attenuation values (median 49.9 vs 55.5HU; p = .018) and had more VAT (242 vs 172 cm 2 ;p = .001). Conventional measures (BMI: p = .729 and waist circumference: p = .356), were not useful in discriminating morbidly obese patients with MS. By multivariable logistic regression, fatty liver infiltration (OR = 5.3; p = .03) and age (OR = 1.08; p = .04) were the only factors independently related to the presence of MS. MS prevalence was 100%, 71% and 55%, respectively for patients with both fatty liver and visceral adiposity; one; or none of this findings (AUC – .715; p = .016). Conclusion: CT scan seems to measure 2 important markers of MS: visceral adiposity and hepatic fatty infiltration. In morbidly obese patients, both visceral adiposity and hepatic fatty infiltration increase the risk for the presence of MS. Highlights: BMI and waist circumference were not useful in discriminating between morbidly obese with and without Metabolic Syndrome. In morbidly obese, the expression of MetS is related to higher liver fat and increased visceral adipose tissue area. CT scan measures 2 important markers of metabolic syndrome: liver fat and visceral adipose tissue. The prevalence of metabolic syndrome in patients with both liver fat and visceral obesity is 100%.